China After Mao - Barnett, A. Doak (Book collections on Project MUSE., 1967)
One of America's leading authorities on China outlines and assesses the implications of the inevitable passing of Mao Tse-tung and the older generation of revolutionary leaders from their position of command in China. Describing the mid-1960's as "a transitional period of great historic significance," the author outlines the basic unsolved problems and unresolved issues that face Peking's leaders, speculates on future changes in Chinese Communist leadership and policies. Part Il of the book presents documents pertinent to the developing crisis in China, including "Khrushchev's Phoney Communism," Lin Piao's "Long Live the Victory of the People's War," and "Great Cultural Revolution." China After Mao is based on the Walter E. Edge lectures given at Princeton University in October 1966. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905